A 52-Year-Old Woman with a Palpable Abdominal Mass - Yang, Yuh-Jeng; Wu, Chin-Chu; Wang, Tzong-Luen; Lin, Aming Chor-Ming (Archives of Academic Emergency Medicine, 2018)
A 52-year-old woman presented with a history of diabetes mellitus under medical treatment and a surgical history of a cesarean section 20 years ago. The patient was referred to our emergency department because of a 2-week hypermenorrhea and unspecific abdominal pain without nausea and vomiting, fever, or other symptoms. She did not complain of weight loss.